The role of crossing boundaries in collaborative open learning in cross-institutional academic development - Chrissi Nerantzi (Research in Learning Technology, 2019)
This paper reports findings relating to boundary-crossing experiences from a phenomenographic study which explored collaborative open learning in two cross-institutional academic development courses. Four of the 11 categories of description and their qualitatively different variations emerged through the analysis and provide new insights into how learners experienced boundary crossing, through modes of participation; time, places and space; culture and language; and diverse professional contexts. Implications and opportunities for academic development linked to boundary crossing are highlighted in this paper, which might also be of use, and relevant to, in other professional areas and disciplines in higher education.